THE EFFECT OF LOCAL AUTONOMY POLICY AND BUDGET ALLOCATION TOWARD THE CAPITAL EXPENDITURE SHARE IN INDONESIA - Muhammad Zilal Hamzah; Tatok Djoko Sudiarto (Universitas Trisakti, 2014)
Today, regional autonomy policy in Indonesia has been running for 12 years. This policy is generally expected to bring a good change to the Indonesian macroeconomics conditions and in particular for the regional economy, can be more independent in the revenue and in the allocation of the budget, which in turn is expected to improve the welfare of its people. This study aimed to examine the effect of regional autonomy, the budget allocation for education, health, housing, foreign aid, tax and salaries share toward the capital expenditure share. This study uses panel data by years of research 1990 - 2011 and consists of a cross section 26 provinces. Based on the results of the study by using a random effect model, statistically the result find the budget allocation for education, housing, health, salaries, foreign aid has a significant effect on the share of capital expenditure, while for regional autonomy and tax share has no effect a significant share of the capital expenditure.Keywords: regional autonomy, the capital expenditure share.